Steroid-Refractory Immune-Related Hepatitis Caused by Pembrolizumab with Stage IVB Non-Small Cell Lung Cancer: A Case Report - Tomomi Hamaguchi; Makoto Ueno; Satoshi Kobayashi; Shun Tezuka; Manabu Morimoto; Terufumi Kato; Haruhiro Saito; Shinya Sato; Junji Furuse; Shin Maeda (Case Reports in Gastroenterology)
Introduction: We report the case of a man in his 50s with stage IVB non-small cell lung cancer who developed severe immune-related hepatitis caused by pembrolizumab. Case Presentation: He received carboplatin, pemetrexed, and pembrolizumab as first-line therapy. After four courses, each of the triplet regimen and maintenance therapy with pemetrexed and pembrolizumab, the patient developed immune-related pneumonitis and colitis. Therefore, pemetrexed and pembrolizumab were discontinued, and 0.5 mg/kg/day prednisolone was started. Despite gradual reduction of the prednisolone to 15 mg/day along with resolution of the pneumonitis and colitis, hepatic dysfunction occurred (elevated serum bilirubin and transaminase levels). We made a diagnosis of immune-related hepatitis based on liver biopsy results and negative results for other causes, such as viral infection. We increased the prednisolone dose to 2 mg/kg/day; however, the hepatic dysfunction was not resolved. Upon sequential methylprednisolone pulse therapy (1,000 mg/day), mycophenolate mofetil, and azathioprine treatment, the hepatic dysfunction plateaued but was not resolved. The patient did not respond to steroids for immune-related hepatitis, developed infectious enteritis owing to a compromised state, and died of sepsis on day 107 after diagnosis of immune-related hepatitis. Conclusion: This case highlights the importance of early diagnosis of steroid-refractory disease, prompt initiation of immunosuppressive agents, and steroid dose reduction in such cases. The changes in liver function during steroid non-response and immunosuppressive drug induction in this case are valuable as a reference for future cases of immune-related adverse event hepatitis.